Protectionism and Gender Inequality in Developing Countries - Artuc, Erhan; Depetris Chauvin, Nicolas; Porto, Guido; Rijkers, Bob (World Bank, Washington, DC, 2021)
How do tariffs impact gender inequality? Using harmonized household survey and tariff data from 54 low- and middle-income countries, this paper shows that protectionism has an anti-female bias. On average, tariffs repress the real incomes of female headed households by 0.6 percentage points relative to that of male headed ones. Female headed households bear the brunt of tariffs because they derive a smaller share of their income from and spend a larger share of their budget on agricultural products, which are usually subject to high tariffs in developing countries. Consistent with this explanation, the anti-female bias is stronger in countries where female-headed households are underrepresented in agricultural production, are more reliant on remittances, and spend a larger share of their budgets on food than male-headed ones.